Local/Regional “Swan Group” and Related Ceramics from Necropolis of Tenedos - Ayaz, Mehmet (Fırat University, 2025)
This study examines the so-called "swan group” and related ceramics found during the past rescue excavations conducted in the 1960s and 1990s, as well as recent excavations carried out between 2021 and 2023 in the necropolis of Tenedos. These ceramics, which were important for the burial rituals in Tenedos from the first half/mid-6th century BC to the 5th century BC, include shapes like miniature-sized skyphos, lekane, phiale, and krateriskos. The purpose of this study is to provide new contributions to the types, decoration styles, and chronology of these ceramic vessels from Tenedos. I divide the ceramics into two groups: Swan Group and Swan Group Related Ceramics, drawing on C. Aslan's observations on similar finds from Troy. The first group, comprising two skyphoi and a lekane, showcases silhouetted animal figures (birds and felines) in silhuette technique, recalling the parallels from the settlements at the mouth of the Hellespontus. Two phialai, a lid, and a krateriskos decorated with simple ornamental elements such as dots, leaves, tongues, and inverted “Z” sequences were evaluated in the second group. The decorative compositions and details of the ceramics in the Tenedos Swan Group align with the "regional" decorative style commonly associated with Northwestern Anatolia/Troad in literature. The differences suggest they may have belonged to different series or to different potters’ workshops.

Bu çalışmada Tenedos nekropolisinde 1950 ve 1990’lı yıllarda yapılan müze kurtarma kazıları ile 2021 yılında başlayan yeni kazılar sırasında bulunan "kuğu grubu" ve bunlarla ilişkili seramik kaplar incelenmektedir. Minyatür boyutlu skyphos, lekane, phiale ve krateriskostan oluşan bu seramik kaplar Tenedos ölü gömme ritüelleri içerisinde MÖ 6. yüzyılın ilk yarısı / ortalarından MÖ 5. yüzyıl içerine kadar yer bulmuşlardır. Çalışmanın amacı bu seramik kapların tiplerine, süsleme tarzlarına ve kronolojilerine Tenedos’tan yeni katkılar sağlamaktır. Kaplar bu çalışmada C. Aslan’ın benzer Troya buluntuları üzerine gözlemlerinden esinlenilerek Kuğu Grubu ve Kuğu Grubu İlişki seramikler olmak üzere iki grupta incelenmiştir. İki skyphos ve bir lekaneden oluşan ilk grup Hellespontos ağzındaki yerleşimlerde ele geçenleri anımsatır şekilde siluet üslupta hayvan (kuş ve kedigil) figürleri ile bezelidir. Aynı teknikte nokta, yaprak, dil, rozet ve ters “Z” dizileri gibi basit süsleme ögeleri ile bezenmiş olan üç phiale, bir kapak ve bir krateriskos ise ikinci grupta değerlendirilmiştir. Tenedos Kuğu Grubu seramikleri, taşıdıkları bezeme kompozisyonları ve bunların işlenişlerindeki detaylarıyla literatürde Kuzeybatı Anadolu / Troas merkezli olabileceği değerlendirilen “bölgesel” bezeme üslubun üyelerinden olmalıdır. Öte yandan, diğer yerleşimlerde bulunanlardan ayrı seriler ya da çömlekçi atölyelerin ürünleri olabileceklerini düşündüren farklılıklar da dikkat çekmektedir.
Tenedos Nekropolisi'nden Yerel/Bölgesel “Kuğu Grubu” ve İlişkili Seramikler
Keywords: Ceramics in Archeology; Arkeolojide Seramik